Social technologies in Rio Grande do Norte: a discussion on the coexistence with Brazil’s semiarid region - Silva, Valdenildo Pedro da; Barros, Evelyn Christie Nascimento de (Sustainability in Debate, 2016)
Social technologies (TS) have been incorporated as an instrument of power in the Brazilian Northeast region, since they carry a strong paradigm-breaking appeal in the matter of combating drought and coexisting with the semiarid climate. However, there are few discussions about these TS. Little is known about the more common and more significant TS; about which are being implemented; about who implements them; about their contributions to nature conservation, to human survival, and to the coexistence of residents with the semiarid region as a whole and specially with the semiarid sections of the state of Rio Grande do Norte. This study discusses the major TS developed and used by the local populations seeking coexistence with the semiarid sections of the state. Bibliographic and documentary research were conducted and interviews were made (by means of phone calls made to the heads of agencies or partner institutions), in order to obtain information on TS applicability, frequency, construction methods and main contributions. The results show that the most common and disseminated TS in Rio Grande do Norte’s semiarid region are focused on the collection and storage of rainwater - the cistern, the flood tank, the underground dam, the dirt trench, the barraginha (small dam), the stone tank and the common pump. These TS help people coexist with the semiarid climate in matters related to the capture and storage of water. However, access to TS and the search for improved patterns of coexistence through more enduring public policies remain as challenges to be overcome by some segments.